PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN (PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2021 – 2023) - Adimas Sutrisno; Yulia Setyarini (J-MACC, 2025)
Corporate value plays a crucial role in the business world, with the realization of optimal corporate value being the main goal that every business entity wants to achieve. This study was conducted with the aim of determining whether independent boards of commissioners, boards of directors, audit committees, institutional ownership, managerial ownership, corporate social responsibility, and intellectual capital have an influence on the valuation of a company. This study was conducted on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the period 2021–2023. The data collection technique used in this study was based on purposive sampling, with a population of 93 companies and a sample of 50 companies. The data processing technique used in this study was SPSS (Statistical Package for the Social Sciences). The findings of this study indicate that independent boards of commissioners influence company value, boards of directors influence company value, audit committees do not influence company value, institutional ownership does not influence company value, managerial ownership influences company value, corporate social responsibility does not influence company value, and intellectual capital does not influence company value. Keywords: Company value, Good corporate governance, Corporate social responsibility, Intellectual capital.